Five-Year Yield Growth Rates of Major Crops in the CGIAR CRP II Priority Countries - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
Yield growth rate (%) of major crop commodities in CGIAR CRP II priority countries were computed using the FAOSTAT-retrieved national crop production statistics data for five most recent years (2009-2013 in most countries; where available, 2014 data was also included).